Lycopodiella cernua (L.) Pic. Serm. (Family : Lycopodiaceae) : an Addition to the Pteridophytic Flora of Nainital Hills - Pangety, Y. P. S.; Martolia, S. Gokul; Tewari, Lalit M. (Indian Forester, 2011)
no abstract